Peningkatan Dimensi Karakter Gotong Royong Melalui Model Pembelajaran Teams Games Tournament pada Mata Pelajaran Pendidikan Pancasila Kelas IV Sekolah Dasar - Ratriastari, Mareta; Hardini, Agustina Tyas Asri (Peneliti.net, 2025)
The purpose of this research is to improve the mutual cooperation attitude of class IV students at SD Negeri Dukuh 01 Salatiga through the application of the Teams Games Tournament (TGT) learning model. Through the Teams Games Tournament (TGT) learning model, students can explore material information from the material presented, learning activities are carried out in groups based on competitions or matches so that they require good teamwork and mutual cooperation to achieve common goals. This research is classroom action research whose research subjects are fourth grade students at SD Negeri Dukuh 01 Salatiga. The research lasted for 2 cycles accompanied by pre-cycle activities. In the pre-cycle activities, the percentage score for the students' mutual cooperation character dimension was 49.66%. In cycle I or after being given action using the Teams Games Tournament (TGT) learning model, the percentage score on the mutual cooperation character dimension increased by 11.14% to 60.80%. In cycle II it increased again by 23.86% to reach a score of 84.66%. From the research results, it can be concluded that the TGT type cooperative learning model can improve students' mutual cooperation character because it can build fun learning activities and increase cooperation between students.